2005
DOI: 10.1111/j.1525-1438.2005.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Parametrial and rectovaginal adenocarcinoma arising from endometriosis

Abstract: Malignant extragonadal tumors arising from endometriosis are rare. We report on two cases. A 41-year-old gravida 1, para 1 (G1P1), with adenocarcinoma of the right parametrium arising from endometriosis and a 51-year-old G1P1 with endometriosis-associated rectovaginal adenocarcinoma were treated. Treatment included radical surgery plus radiation therapy. While the former patient was doing well 2 years after the primary diagnosis, the latter suffered a local pelvic recurrence 2 years later. Although there are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 14 publications
0
30
0
7
Order By: Relevance
“…Nevertheless, it was possible that the rectovaginal septum tumor was a primary serous adenocarcinoma concurrent with fallopian-tube carcinoma, because there are approximately 20 reports of primary adenocarcinomas of the rectovaginal septum, although most of them are endometrioid adenocarcinoma associated with deep endometriosis [2]. To resolve this issue, we analyzed the mutational status of TP53, as somatic mutations are commonly observed in serous adenocarcinoma of the ovaries, fallopian tube, and peritoneum [3].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it was possible that the rectovaginal septum tumor was a primary serous adenocarcinoma concurrent with fallopian-tube carcinoma, because there are approximately 20 reports of primary adenocarcinomas of the rectovaginal septum, although most of them are endometrioid adenocarcinoma associated with deep endometriosis [2]. To resolve this issue, we analyzed the mutational status of TP53, as somatic mutations are commonly observed in serous adenocarcinoma of the ovaries, fallopian tube, and peritoneum [3].…”
Section: Discussionmentioning
confidence: 99%
“…Ulrich U. et al [5] reported that the most frequent site in 139 cases of extra-ovarian cancer arising from endometriosis was the bowel (28%), followed by the rectovaginal septum (13%), uterus (arising from adenomyosis) (12%), peritoneum (6%) and others (such as broad ligament, parametrium, urinary bladder, and vagina) (44%). Reviews on the histology of malignant transformation in extra-ovarian endometriosis are primarily represented by endometrioid adenocarcinoma (69.1%), followed by sarcoma (25%) and clear cell carcinoma (4.5%) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Einige Typen des Ovarialkarzinoms und die ovarielle Endometriose teilen sich gewisse Eigenschaften, und zwar lokale Invasion, Neoangiogenese mit erhöhter VEGF ("vascular endothelial growth factor")-Expression, Lymphangiogenese, Resistenz gegenüber Apoptosemechanismen, COX2-Überexpression und genomische Instabilität [17,37,42,43,45]. Von den endometrioseassoziierten Malignomen sind 80 % Ovarialkarzinome, etwa 20 % betreffen extragonadale Manifestationen [10,15,19].…”
Section: Histologie Und Pathogeneseunclassified
“…Therapie der Wahl endometrioseassoziierter Malignome -sowohl EAOC als auch der extragonadalen EAM -besteht in der Resektion im Gesunden; die EAOC werden dabei dem leitliniengerechten operativen Staging unterzogen [42,46]. Die komplette chirurgische Entfernung ist fast immer gut durchführ-bar, da extrapelvine Manifestationenim Gegensatz zu den high-grade serösen Ovarialkarzinomen, die ja in der Mehrzahl im Stadium FIGO III diagnostiziert werden -bei diesen Tumoren selten sind.…”
Section: Bisherige Klinische Bedeutungunclassified
See 1 more Smart Citation